Muhammad Abduh’s Role in al-Waqa’i‘ al-Misriyyah an Official Egyptian Gazette - Ahmad Nabil Amir; Tasnim Abdul Rahman (Taqrib : Journal of Islamic Studies and Education, 2025)
The article discusses the role of Muhammad Abduh (1849-1905) in his illustrious career as leading editor of al-waqa'i al-misriyyah (Egyptian events) an official Egyptian gazette.